Halal Authentication and Metabolite Mapping of Kombucha Products via Gas Chromatography-Mass Spectrometry (GC-MS) and Chemometric Analysis - Hermanto, Sandra; Arginia, Della; Mustafidah, Mabrurotul; Fathoni, Ahmad (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
The presence of ethanol in fermented beverages is a critical factor in the halal certification process. One of the key parameters for verifying the halal status of such products is the quantification of ethanol content. Kombucha tea, a fermented beverage produced from sugared tea and a Symbiotic Culture of Bacteria and Yeast (SCOBY), naturally contains ethanol as a byproduct of fermentation. This study aims to determine the ethanol content and differentiate the metabolite profiles of kombucha tea using a non-targeted metabolomics approach, based on variations in tea type, storage temperature, and duration. Ethanol levels were measured by gas chromatography, and metabolite profiling was conducted by gas chromatography–Mass Spectrometry (GC-MS), followed by Principal Component Analysis (PCA) to visualize compositional differences and identify characteristic compounds. The results indicated that tea type significantly influenced ethanol production. The ethanol content of kombucha prepared with black tea, green tea, and white tea was 0.1126% w/w ± 0.0003 v/v, 0.1708% w/w ± 0.0053 v/v, and 0.1301% w/w ± 0.0043 v/v, respectively. Green tea kombucha, which exhibited the highest ethanol content, was selected for storage analysis. During storage, ethanol levels increased slightly to 0.1789% w/w ± 0.0008 v/v in the first week, followed by a gradual decline to 0.1478% w/w ± 0.0071 v/v by the fourth week. Metabolomic profiling revealed distinct differences in secondary metabolite composition among the three tea variants, as evidenced by non-overlapping PCA groupings. Key discriminant compounds identified included ethyl acetate, ethyl octanoate, ethylamine, and (E)-2-decenal, which are proposed as characteristic markers for kombucha derived from black, green, and white teas. These findings contribute to understanding kombucha’s biochemical diversity and support halal verification through ethanol quantification and metabolite-based authentication.